2017
DOI: 10.1111/dom.12827
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term mortality after acute myocardial infarction among individuals with and without diabetes: A systematic review and meta‐analysis of studies in the post‐reperfusion era

Abstract: Despite medical advances, individuals with diabetes have a 50% greater long-term mortality compared with those without. Further research to understand the determinants of this excess risk are important for public health, given the predicted rise in global diabetes prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 94 publications
(228 reference statements)
1
17
0
4
Order By: Relevance
“…A recent meta-analysis 35 demonstrated that individuals with DM have a 50% greater long-term mortality compared with those without. Nedkoff et al 36 also mentioned that even though a number of studies have reported a temporal decrease in excess all-cause mortality in the broader diabetic population, studies confined that patients with MI have shown limited improvement in the excess long-term mortality associated with DM.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis 35 demonstrated that individuals with DM have a 50% greater long-term mortality compared with those without. Nedkoff et al 36 also mentioned that even though a number of studies have reported a temporal decrease in excess all-cause mortality in the broader diabetic population, studies confined that patients with MI have shown limited improvement in the excess long-term mortality associated with DM.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes is a primary risk factor for cardiovascular disease, substantially increasing the risk of both coronary heart disease and stroke [ 1 , 2 , 3 ]. Moreover, all-cause mortality is 50% higher in diabetics than their counterparts following myocardial infarction [ 4 ]. Unfortunately, the prevalence of diabetes is increasing, with 11.9% of the U.S. adult population currently diseased compared to just a few decades ago when the prevalence was 8.8% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients approximately 30% who underwent PCI suffer from diabetes ( 13 ). Considering the counter-balancing effects of hemorrhagic and ischemic complications, the recent ultra-short DAPT strategy may not be suitable for patients with T2DM ( 15 ). New-onset of diabetes after PCI (NODAP) has attracted much attention; a 5-year survival of patients after revascularization with diabetes were worse ( 16 ).…”
Section: Introductionmentioning
confidence: 99%